Breed difference in acquired resistance of sheep to Haemonchus contortus - YADAV, C L; SINGH, Z; BANERJEE, D P; CHATURVEDI, G C (The Indian Journal of Animal Sciences, 2013)
Parasitological, pathophysiological and immunological parameters were compared between a-year-old domestic Nali and Merino crossbred sheep experimentally infected with Haemonchus contortus. The natural gastrointestinal nematode infection acquired during the previous grazing season over a period of 6 months on pasture was terminated by anthelmintic treatment and both the breeds were then reinfected experimentally with H. contortus. No significant differences were found between the breeds in egg count and worm burden except that Nali sheep shed significantly fewer eggs on day 27 following reinfection. Likewise, no significant differences in the value of haemoglobin, packed-cell volume. total serum proteins, calcium and phosphorus levels were noticed between the 2 breeds. nor any difference detected as regards the gamma globulin levels skin thickness and cellular response at the local sites and abomasal mucosa.